2004
DOI: 10.1016/s0002-9394(03)01279-0
|View full text |Cite
|
Sign up to set email alerts
|

Vitrectomy and internal limiting membrane peeling for myopic foveoschisis*1

Abstract: Vitrectomy with vitreous cortex removal, ILM peeling, and gas tamponade could be useful to treat myopic foveoschisis in highly myopic eyes. Because the natural course of the disease is not well-understood, further study should establish indications for this surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…On the other hand, certain studies have demonstrated the effect of vitrectomy without ILM peeling (21,23,33). However, the majority of studies that have investigated ILM peeling are either case series or case reports (34), with very few studies comparing the two methods (35). The results of the present study suggested that ILM peeling may be the preferable method, and this result is consistent with the study which compared vitrectomy with and without ILM peeling by Taniuchi et al (24), which additionally demonstrated that tractional macular detachment developed more frequently in eyes without ILM peeling.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, certain studies have demonstrated the effect of vitrectomy without ILM peeling (21,23,33). However, the majority of studies that have investigated ILM peeling are either case series or case reports (34), with very few studies comparing the two methods (35). The results of the present study suggested that ILM peeling may be the preferable method, and this result is consistent with the study which compared vitrectomy with and without ILM peeling by Taniuchi et al (24), which additionally demonstrated that tractional macular detachment developed more frequently in eyes without ILM peeling.…”
Section: Discussionmentioning
confidence: 99%